Political Influence on German Banking Supervision and Its Impact on Economic Growth: Empirical Evidence from Survey Data - Jovanovic, Mario (Journal of Reviews on Global Economics, 2012)
Abstract: Based on survey data, this paper investigates the impact of politically dependent banking supervision on the perception of financial uncertainty. There is empirical evidence that political influence has only marginal influence on the level of financial uncertainty. Introducing the unobservable construct "fundamental uncertainty", which is motivated by the implicit association test of Greenwald, McGhee, and Schwartz (1998), politically dependent supervision leads to financial expectations, which are influenced by economic policy. Therefore, only dependent banking supervision implements a link between political decisions and fundamental uncertainty and, finally, economic growth.